Balancing the modulation of soy protein structure to achieve improved texture and reduced antigenicity in soy yogurt: A practical approach of proteolytic pretreatment and lactic acid bacteria fermentation - Qiyuan Lu; Xinran Guo; Xia Fan; Benjamin K. Simpson; Wei Li; Xin Rui (Food Chemistry, 2026)

High incidence of estrous cycle irregularities in heterogeneous stock (HS) rats is associated with footshock-resistant cocaine intake - Elizabeth A. Sneddon; Supakorn Chonwattanagul; Kathleen Bai; Pranav H. Kurup; Sonja L. Plasil; Michelle R. Doyle; Sélène Zahedi; Sierra Simpson; Benjamin C. Sichel; Dyar N. Othman; Molly Brennan; Abraham A. Palmer; et al. (Psychopharmacology, 2026)
Rationale Hormonal fluctuations throughout the estrous cycle are hypothesized to influence drug-related behaviors. Preclinical models show that some cocaine-related behaviors are influenced by the estrous cycle. However, the extent to which the estrous cycle modulates cocaine self-administration in outbred heterogeneous stock (HS) rats is unknown. Objectives We aimed to examine the relationship between estrous phases and cocaine self-administration behavior in HS rats using an operant model of extended access to cocaine self-administration. Methods We assessed the escalation of intake, breaking point, and resistance to foot shock. Using vaginal swabbing and lavage techniques, we characterized the relationship between estrous phase and cocaine behaviors. We then comprehensively evaluated estrous cycling patterns in young adult and adult HS rats, comparing them with Wistar rats. Results Estrous phase showed no association with cocaine self-administration in HS rats. 82% of female HS rats exhibited irregular estrous cycling with variability to the phase length, even in the absence of drug exposure, a phenomenon not observed in the Wistar strain. Females with irregular cycling showed greater footshock-resistant cocaine intake. Conclusions This study provides the first evidence that most female HS rats exhibit irregular estrous cycling. In HS rats, the estrous phase per se has no major influence on cocaine self-administration, whereas cycling irregularity was associated with specific addiction-related behaviors, including footshock-resistant intake. As HS rats gain popularity in behavioral and genome-wide studies, understanding these cycle disruptions is crucial as they may reveal genetic links into cycling variability and individual differences to aspects of cocaine use.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Assessing behavioural economic demand for morphine after an acute dose in individuals with- and without childhood trauma: a double-blind, randomised, controlled trial - Martin Trøstheim; Benjamin L. Berey; Elizabeth R. Aston; Matthew J. Gullo; Lee Hogarth; Graham Simpson; Rupert Broomby; Celia J. Morgan; Molly Carlyle (Psychopharmacology, 2025)
Background Childhood trauma is associated with positive subjective responses to acute opioids in the laboratory. Yet, its impact on behavioural economic demand for opioids remains unclear. Because demand can predict future use and misuse, we investigated whether individuals with childhood trauma also display greater demand for opioids in the laboratory. Methods This secondary analysis used data from a double-blind, randomised, controlled, counterbalanced trial. Across two sessions, individuals with ( n = 26) and without ( n = 21) childhood trauma received a high (0.15 mg/kg) and low (0.01 mg/kg) dose of intramuscular morphine 120 min before a hypothetical purchase task. Participants also regularly reported their subjective desire for the study drug. Area under the consumption and expenditure curves, and specific demand indices ( O max , P max , breakpoint , intensity , elasticity ), were analysed with non-parametric mixed models. Results Consumption and expenditure for low dose morphine was lower in the childhood trauma group when compared to high dose morphine in this group, and low dose morphine in the control group ( p s ≤ 0.03). Consistent results were obtained for specific demand indices O max , P max , and breakpoint , but not intensity or elasticity . Positive correlations between subjective desire and consumption and expenditure were only observed in the childhood trauma group ( Tau-c = 0.24–0.34, p s ≤ 0.03). Conclusion Under laboratory conditions, desires to use opioids among individuals with childhood traumas may not manifest in strong intentions to acquire these drugs. Diverging results from psychometric measures of subjective and economic opioid value highlight the need for future research to explore contextual and resilience factors to understand how problematic opioid use emerges after childhood traumas.

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Reporting population size in wastewater-based epidemiology: A scoping review - Mackay Price; Bradley S. Simpson; Benjamin J. Tscharke; Fahad Ahmed; Emma L. Keller; Hannah Sussex; Melanie Kah; Katarzyna Sila-Nowicka; Andrew Chappell; Cobus Gerber; Sam Trowsdale (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Monitoring the use of novel psychoactive substances in Australia by wastewater-based epidemiology - Emma L. Jaunay; Richard Bade; Kara R. Paxton; Dhayaalini Nadarajan; Daniel C. Barry; Yuze Zhai; Benjamin J. Tscharke; Jake W. O'Brien; Jochen Mueller; Jason M. White; Bradley S. Simpson; Cobus Gerber (Science of The Total Environment, 2024)

Construction of hypoallergenic microgel by soy major allergen β-conglycinin through enzymatic hydrolysis and lactic acid bacteria fermentation - Yumeng Fu; Xinran Guo; Wei Li; Benjamin K. Simpson; Xin Rui (Food Research International, 2024)

Distinct dynamics of plant- and microbial-derived soil organic matter in relation to varying climate and soil properties in temperate agroecosystems - Meiling Man; Edward G. Gregorich; Michael H. Beare; Benjamin H. Ellert; Myrna J. Simpson (Geochimica et Cosmochimica Acta, 2023)

Modulation of soy protein immunoreactivity by different matrix structures of lactic acid bacterium-induced soy protein gels: Epitope destruction during in vitro gastroduodenal digestion and absorption - Yaqiong Wang; Yumeng Fu; Wei Li; Benjamin K. Simpson; Xin Rui (Food Research International, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

SCUBA noise alters community structure and cooperation at Pederson’s cleaner shrimp cleaning stations - Kieran P. McCloskey; Andrew N. Radford; Amelia Rose; Giorgio Casiraghi; Natalie Lubbock; Emma Weschke; Benjamin M. Titus; Dan A. Exton; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Recreational SCUBA diving is widespread and increasing on coral reefs worldwide. Standard open-circuit SCUBA equipment is inherently noisy and, by seeking out areas of high biodiversity, divers inadvertently expose reef communities to an intrusive source of anthropogenic noise. Currently, little is known about SCUBA noise as an acoustic stressor, and there is a general lack of empirical evidence on community-level impacts of anthropogenic noise on coral reefs. Here, we conducted a playback experiment on Caribbean reefs to investigate impacts of SCUBA noise on fish communities and interspecific cooperation at ecologically important cleaning stations of the Pederson’s cleaner shrimp Ancylomenes pedersoni . When exposed to SCUBA-noise playback, the total occurrence of fishes at the cleaning stations decreased by 7%, and the community and cleaning clientele compositions were significantly altered, with 27% and 25% of monitored species being affected, respectively. Compared with ambient-sound playback, SCUBA-noise playback resulted in clients having to wait 29% longer for cleaning initiation and receiving 43% less cleaning; however, cheating, signalling, posing and time spent cleaning were not affected by SCUBA-noise playback. Our study is the first to demonstrate experimentally that SCUBA noise can have at least some negative impacts on reef organisms, confirming it as an ecologically relevant pollutant. Moreover, by establishing acoustic disturbance as a likely mechanism for known impacts of diver presence on reef animals, we also identify a potential avenue for mitigation in these valuable ecosystems.

Pectin from plantain peels: Green recovery for transformation into reinforced packaging films - Jiayu Xie; Yi Zhang; Sappasith Klomklao; Benjamin K. Simpson (Waste Management, 2023)

Impact of Limited Degree of Freedom Drag Coefficients on a Floating Offshore Wind Turbine Simulation - Arjun Srinivas; Bryson Robertson; Jonah Benjamin Gadasi; Barbara Gwynne Simpson; Pedro Lomónaco; Jesús María Blanco Ilzarbe (Journal of Marine Science and Engineering, 2023)
The worldwide effort to design and commission floating offshore wind turbines (FOWT) is motivating the need for reliable numerical models that adequately represent their physical behavior under realistic sea states. However, properly representing the hydrodynamic quadratic damping for FOWT remains uncertain, because of its dependency on the choice of drag coefficients (dimensionless or not). It is hypothesized that the limited degree of freedom (DoF) drag coefficient formulation that uses only translational drag coefficients causes mischaracterization of the rotational DoF drag, leading to underestimation of FOWT global loads, such as tower base fore-aft shear. To address these hydrodynamic modeling uncertainties, different quadratic drag models implemented in the open-source mid-fidelity simulation tool, OpenFAST, were investigated and compared with the experimental data from the Offshore Code Comparison Collaboration, Continued, with Correlation (OC5) project. The tower base fore-aft shear and up-wave mooring line tension were compared under an irregular wave loading condition to demonstrate the effects of the different damping models. Two types of hydrodynamic quadratic drag formulations were considered: (1) member-based dimensionless drag coefficients applied only at the translational DoF (namely limited-DoF drag model) and (2) quadratic drag matrix model (in dimensional form). Based on the results, the former consistently underestimated the 95th percentile peak loads and spectral responses when compared to the OC5 experimental data. In contrast, the drag matrix models reduced errors in estimates of the tower base shear peak load by 7–10% compared to the limited-DoF drag model. The underestimation in the tower base fore-aft shear was thus inferred be related to mischaracterization of the rotational pitch drag and the heave motion/drag by the limited-DoF model.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Validated Guidelines for Simulating Centrifugal Blood Pumps - Clayton S. Semenzin; Benjamin Simpson; Shaun D. Gregory; Geoff Tansley (Cardiovascular Engineering and Technology, 2021)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Food-related transglutaminase obtained from fish/shellfish - Yi Zhang; Benjamin K. Simpson (Critical Reviews in Food Science and Nutrition, 2020)

White matter damage, neuroinflammation, and neuronal integrity in HAND - Aljoharah Alakkas; Ronald J. Ellis; Caitlin Wei-Ming Watson; Anya Umlauf; Robert K. Heaton; Scott Letendre; Ann Collier; Christina Marra; David B. Clifford; Benjamin Gelman; Ned Sacktor; Susan Morgello; et al. (Journal of NeuroVirology, 2019)

Phaseolus vulgaris lectins: A systematic review of characteristics and health implications - Shudong He; Benjamin K. Simpson; Hanju Sun; Michael O. Ngadi; Ying Ma; Tiemin Huang (Critical Reviews in Food Science and Nutrition, 2018)

Evaluating the accuracy of self-report for the diagnosis of HIV-associated neurocognitive disorder (HAND): defining “symptomatic” versus “asymptomatic” HAND - Lisa C. Obermeit; Jessica Beltran; Kaitlin B. Casaletto; Donald R. Franklin; Scott Letendre; Ronald Ellis; Christine Fennema-Notestine; Florin Vaida; Ann C. Collier; Christina M. Marra; David Clifford; Benjamin Gelman; et al. (Journal of NeuroVirology, 2017)

Apolipoprotein E ε4 genotype status is not associated with neuroimaging outcomes in a large cohort of HIV+ individuals - Sarah A. Cooley; Robert H. Paul; Christine Fennema-Notestine; Erin E. Morgan; Florin Vaida; Qianqian Deng; Jie Ashley Chen; Scott Letendre; Ronald Ellis; David B. Clifford; Christina M. Marra; Ann C. Collier; et al. (Journal of NeuroVirology, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

Long-term efavirenz use is associated with worse neurocognitive functioning in HIV-infected patients - Qing Ma; Florin Vaida; Jenna Wong; Chelsea A. Sanders; Yu-ting Kao; David Croteau; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; Justin C. McArthur; Susan Morgello; et al. (Journal of NeuroVirology, 2016)

CSF biomarkers of monocyte activation and chemotaxis correlate with magnetic resonance spectroscopy metabolites during chronic HIV disease - Albert M. Anderson; Christine Fennema-Notestine; Anya Umlauf; Michael J. Taylor; David B. Clifford; Christina M. Marra; Ann C. Collier; Benjamin B. Gelman; Justin C. McArthur; J. Allen McCutchan; David M. Simpson; Susan Morgello; et al. (Journal of NeuroVirology, 2015)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

Volcanology and petrology of Mathews Tuya, northern British Columbia, Canada: glaciovolcanic constraints on interpretations of the 0.730 Ma Cordilleran paleoclimate - Benjamin R. Edwards; James K. Russell; Kirstie Simpson (Bulletin of Volcanology, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Purification and properties of digestive lipases from Chinook salmon (Oncorhynchus tshawytscha) and New Zealand hoki (Macruronus novaezelandiae) - Ivan Kurtovic; Susan N. Marshall; Xin Zhao; Benjamin K. Simpson (Fish Physiology and Biochemistry, 2010)

The Role of Cohort Studies in Drug Development: Clinical Evidence of Antiviral Activity of Serotonin Reuptake Inhibitors and HMG-CoA Reductase Inhibitors in the Central Nervous System - Scott L. Letendre; Jennifer Marquie-Beck; Ronald J. Ellis; Steven Paul Woods; Brookie Best; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina Marra; Justin C. McArthur; J. Allen McCutchan; Susan Morgello; et al. (Journal of Neuroimmune Pharmacology, 2007)